2020
DOI: 10.36483/vanvetj.547457
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Used Immunostimulating Drugs with FMD Vaccine on Immunoglobulins in Sheep

Abstract: In this study, the effect of used immunostimulating drugs with FMD vaccine on immunoglobulins was aimed to investigate in sheep. For this purpose 40 healthy sheep were divided into 4 groups. Blood and serum samples were taken from all animals from 0 days before the study. Blood samples were measured immediately, and IgA, IgG, IgM, IgE and Zn values from biochemical parameters were stored for measurement. Group I was applied only FMD vaccine, group II Levamisole with the FMD vaccine, group III Zinc with FMD vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In addition, in terms of globulin values, there has also significant difference (P<0.01). These data obtained show that LMS strengthens the immune system by causing an increase in Ig levels such as IgG and IgM and this time are in accordance with the reports of Abdullah and Basbugan (2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, in terms of globulin values, there has also significant difference (P<0.01). These data obtained show that LMS strengthens the immune system by causing an increase in Ig levels such as IgG and IgM and this time are in accordance with the reports of Abdullah and Basbugan (2020).…”
Section: Discussionsupporting
confidence: 91%
“…The studies on levamisole administration have shown an overall increase in Ig levels. Abdullah and Basbugan (2020) showed that IgM levels in sheep increased but it was not statistically significant, IgG levels, on the other hand, increased both numerically and gave a statistically significant result. In this study, it was determined that there was a numerical tendency to increase in IgG values within the Group C (P>0.05), and a significant numerical increase was observed (P˂0.01) in the group-based general evaluation compared to the Group F. Comparing the IgM data of the Group C and F, the difference on the 7 th day was statistically significant (P<0.01), and the comparison of evaluations of group-based regarding the Group C and F indicated that there was a differences between them (P˂0.05).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The amount of IgG in serum of the cattle groups (µg/mL) Those with different letters in the same row in the range of P<0.05 were found to be statistically significant It is thought that the increase in monocytes in the levamisolevaccine group could be due to the stimulating effect of levamisole on macrophages for antigens Abdullah and Başbuğan (2020). reported that the FMD vaccine in combination with 5 mg/kg levamisole decreased the number of monocytes.…”
mentioning
confidence: 93%